2008
DOI: 10.1111/j.1744-7348.2007.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant resistance against broomrapes (Orobanche spp.): defence reactions and mechanisms of resistance

Abstract: Over 4000 species of angiosperms are able to directly invade and parasitise other plants, but only very few are weedy and parasitise cultivated plants. Together with the witchweeds (Striga spp.) and dodders (Cuscuta spp.), the broomrapes (Orobanche spp.) affect important crops causing complete yield loses with severe infestations. Genetic resistance to parasitisation remains as one of the most desirable components in an integrated control strategy. However, breeding for resistance is a difficult task and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 55 publications
(66 reference statements)
1
43
0
Order By: Relevance
“…plantÁplant pathogenic interactions (Pe´rez-de-Luque et al 2008) and root nodules). Considering the tissue and cellular complexity of an ectomycorrhiza, LM technology could also be very useful to collect the two specific fungal compartments separately (the mantle and the Hartig net) which are expected to be functionally different, at least in terms of nutrient uptake and transport (Nehls et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…plantÁplant pathogenic interactions (Pe´rez-de-Luque et al 2008) and root nodules). Considering the tissue and cellular complexity of an ectomycorrhiza, LM technology could also be very useful to collect the two specific fungal compartments separately (the mantle and the Hartig net) which are expected to be functionally different, at least in terms of nutrient uptake and transport (Nehls et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the host plant can respond to the attack by inducing callose deposition, suberization, lignification, as well as accumulating and secreting toxic compounds (allelochemicals) into the rhizosphere in order to impede the penetration of the parasite within the roots [12]. All these defense mechanisms are regulated to some extent by phytohormones; however there is very little information regarding the specific role and the regulation of these hormones during the plant-parasitic plant interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the radicle penetrates into the host root establishing a connection with the vascular tissues through the haustorium, which serves as an attachment organ [11]. Through the haustorium, the parasitic plant obtains water, nutrients and other substances from the host needed for its own growth and development [11,12], and that negatively affects plant fitness and crop yield. Upon the initial vascular connection, the parasite develops a tubercle, a swelling in the young parasite above the host root, being this the first specific step of parasitic plant growth (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These parasitic weeds attack the roots and connect to the vascular tissues of the host plant, through a specialized structure called haustorium (Parker and Riches, 1993;Joel et al, 2007;Pérez-de-Luque et al, 2008). This allows for an intense exchange of substances among the two biota, including water, minerals and carbohydrates, which can cause severe damage to the host plant and premature death (Mauromicale et al, 2005a;Joel et al, 2007).…”
Section: Introductionmentioning
confidence: 98%